Ethics in Gene Editing - Diana, I Made (Open Access Indonesian Journal of Medical Reviews, 2021)
For thousands of years, humans have felt the need to understand the world around them—and ultimately manipulate it to best serve their needs. There are always ethical questions to address, especially when the manipulation involves the human genome. There is currently an urgent need to actively pursue those conversations as com- mercial gene sequencing and editing technologies have become more accessible and affordable. Gene Editing has enormous potential both as a research tool and a therapeutic intervention. While other types of gene editing are relatively uncontroversial, gene editing has been strongly resisted.